A self-lubricating and highly corrosion-resistant composite coating, its preparation method and application
By introducing solid-liquid reversible lubricating phase into the ceramic-fluoride-based composite coating and vacuum impregnation technology, the poor bonding and corrosion problems of traditional coatings under harsh conditions are solved, and higher corrosion resistance and friction performance are achieved.
Patent Information
- Application Number
- CN202411824319.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The traditional ceramic-fluoropolymer composite coating has poor bonding under harsh friction conditions and has pores and microcracks, causing corrosive media to directly reach the metal matrix and affecting service life.
The ceramic-fluoride-based composite coating is prepared by thermal spraying technology, and the solid-liquid reversible lubricating phase is penetrated into the structural defects of the coating through a vacuum impregnation process, and solidifies and retains after cooling, thereby enhancing adhesion and corrosion resistance.
The corrosion resistance and friction properties of the composite coating are improved, forming a friction film with low shear strength, high hardness, and high elastic modulus, ensuring long-term and effective lubrication in seawater and atmospheric environments, and significantly extending service life.
Smart Images

Figure CN119287304B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite coating materials, and in particular to a self-lubricating strong anti-corrosion composite coating and a preparation method and application thereof. Background Art
[0002] In the field of marine engineering, equipment such as ships, offshore wind farms and drilling platforms often face problems such as chemical and electrochemical corrosion and friction and wear. In the splash zone, which is an alternating dry and wet environment, it is more difficult to prevent wear and the corrosion problem of components is more serious. Ceramic-fluoride composite coatings have low friction coefficients, high wear resistance, good stability and non-adhesion in both atmospheric and seawater environments, and are expected to be used to protect marine engineering equipment in marine environments.
[0003] However, due to the differences in physical and chemical properties between fluoropolymers and ceramic materials, the traditional preparation method requires two steps. First, the ceramic coating is prepared using thermal spraying technology, and then, based on these ceramic coatings, the fluoropolymer is introduced by post-treatment methods such as texturing + impregnation / hot pressing. In the fluoropolymer-ceramic composite coatings prepared by this method, the adhesion between the fluoropolymer and the ceramic material is weak. Under harsh friction conditions, the problem of poor bonding may affect the stability of the composite coating. Another way is to use a one-step method to prepare a ceramic-fluoropolymer composite coating. Although this method can solve the problem of poor bonding between fluoropolymers and ceramic materials to a certain extent, the composite coating has defects such as pores and microcracks. The presence of such defects can allow the corrosive medium to reach the metal substrate directly, causing severe corrosion, which is difficult to meet the service requirements in the marine environment.
[0004] Therefore, there is an urgent need to improve the ceramic-fluoropolymer composite coating so as to extend the service life of the composite coating in seawater or in an alternating environment of seawater and atmosphere.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a self-lubricating strong anti-corrosion composite coating and its preparation method and application, so as to solve or improve the above technical problems.
[0007] The present invention can be implemented like this:
[0008] In a first aspect, the present invention provides a method for preparing a self-lubricating and highly anti-corrosion composite coating, comprising the following steps: preparing a ceramic-fluoride-based composite coating on the surface of a metal substrate to obtain an intermediate material; placing the intermediate material in a liquid formed by heating and melting a solid-liquid reversible lubricating phase for vacuum impregnation, so that the solid-liquid reversible lubricating phase that has become liquid penetrates into the structural defects of the ceramic-fluoride-based composite coating; and then naturally cooling and solidifying so that the solid-liquid reversible lubricating phase solidifies and remains in the structural defects.
[0009] In an optional embodiment, the preparation of the ceramic-fluoride based composite coating includes at least one of the following features:
[0010] Feature 1: The ceramic-fluoride based composite coating is prepared by thermal spraying;
[0011] Feature 2: The thickness of the ceramic-fluoride based composite coating is 100 μm to 300 μm;
[0012] Feature 3: The ceramic-fluoride based composite coating includes an oxide ceramic-fluoride composite coating, a carbide ceramic-fluoride composite coating or a nitride ceramic-fluoride composite coating;
[0013] Feature 4: The raw materials for preparing the ceramic-fluoride-based composite coating include ceramic particles and fluoride particles, wherein the particle sizes of the ceramic particles and the fluoride particles are independently 5μm~75μm, and the mass ratio of the ceramic particles to the fluoride particles is 1:0.2 to 1:1.
[0014] In an optional embodiment, the ceramic-fluoride-based composite coating is prepared by atmospheric plasma spraying;
[0015] Among them, the process parameters of atmospheric plasma spraying include: plasma spray gun current is 450A~650A, argon flow rate is 30L / min~45L / min, hydrogen flow rate is 4L / min~10L / min, spraying distance is 100mm~150mm, and powder feeding rate is 5g / min~25g / min.
[0016] In an alternative embodiment, the fluoride particles include soluble polytetrafluoroethylene particles;
[0017] And / or, the solid-liquid reversible lubricating phase includes at least one of palm wax, microcrystalline wax and stearic acid.
[0018] In an optional embodiment, the temperature of heating and melting is 70°C to 300°C.
[0019] In an optional embodiment, the vacuum impregnation is performed at a pressure of -0.040 MPa to -0.100 MPa for 40 min to 60 min.
[0020] In an optional embodiment, the intermediate material is first subjected to surface polishing, ultrasonic treatment, and drying treatment, and then placed in a liquid formed by heating and melting the solid-liquid reversible lubrication phase.
[0021] In a second aspect, the present invention provides a self-lubricating and highly anti-corrosion composite coating, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0022] In a third aspect, the present invention provides an application of a self-lubricating strong anti-corrosion composite coating as described in the aforementioned embodiment, which can be used, for example, to prepare equipment used in seawater or in an environment where seawater and atmosphere alternate.
[0023] In a fourth aspect, the present invention provides a marine engineering equipment, the manufacturing material of which includes the self-lubricating and highly anti-corrosion composite coating of the aforementioned embodiment.
[0024] The beneficial effects of the present invention include:
[0025] The preparation method of the self-lubricating strong anti-corrosion composite coating provided by the present invention is to use the thermal sprayed ceramic-fluoride composite coating as a template, introduce a solid-liquid reversible lubricating phase, heat and melt the solid-liquid reversible lubricating phase, and then use a vacuum impregnation process to make the melted solid-liquid reversible lubricating phase penetrate into the inherent pores and cracks inside the ceramic coating, and solidify and remain in the above defects after cooling. The preparation method is simple, fast, and efficient, and can greatly improve the corrosion resistance of the composite coating while further reducing the friction coefficient of the coating, thereby achieving the unified performance of the tribological performance and corrosion resistance of the thermal sprayed ceramic-fluoride composite coating.
[0026] When the self-lubricating strong anti-corrosion composite coating is applied to the friction working condition, the fluoride in the composite coating can form a friction film with low shear strength, high hardness, high elastic modulus and strong resistance to plastic deformation on the friction surface, and the solid-liquid reversible lubricating phase retained in the pores and cracks by vacuum impregnation can play a lubricating role together with the fluoride, and the impregnated solid-liquid reversible lubricating phase can continuously overflow to replenish the lubricating film during the subsequent friction process, and the two lubricating phases jointly ensure that the composite coating is effectively lubricated in both the atmosphere and seawater environments for a long time. In addition, the self-lubricating strong anti-corrosion composite coating provided by the present invention has relatively tortuous pores, making it difficult for the corrosive medium to invade the substrate, and the solid-liquid reversible lubricating phase melts and penetrates into the micro / nanoscale defects of the coating in liquid form under the action of vacuum, and can further block the corrosion channel of the corrosive medium after natural cooling to solid, greatly improving the corrosion resistance of the composite coating, and can still maintain the lubrication function under the atmosphere and seawater after ultra-long corrosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 The scanning electron microscope images of the AT3 / PFA composite coating and the AT3 / PFA / CW composite coating in Example 1 of the present invention are shown;
[0029] Figure 2 1 is a diagram showing the element distribution results of the AT3 / PFA / CW composite coating in Example 1 of the present invention;
[0030] Figure 3 The friction coefficient results of the composite coatings prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 7 in the atmospheric environment and the seawater environment;
[0031] Figure 4 The electrochemical impedance spectra of the composite coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 3 of the present invention are shown;
[0032] Figure 5 The friction coefficient results of the composite coatings prepared in Example 1, Comparative Example 2 and Comparative Example 3 of the present invention in the atmospheric environment and the seawater environment after salt spray corrosion. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] The self-lubricating strong anti-corrosion composite coating provided by the present invention and its preparation method and application are described in detail below.
[0035] The invention provides a method for preparing a self-lubricating strong anti-corrosion composite coating, comprising the following steps: preparing a ceramic-fluoride-based composite coating on the surface of a metal substrate to obtain an intermediate material; placing the intermediate material in a liquid formed by heating and melting a solid-liquid reversible lubricating phase for vacuum impregnation, so that the solid-liquid reversible lubricating phase penetrates into the structural defects of the ceramic-fluoride-based composite coating; and then cooling and solidifying, so that the solid-liquid reversible lubricating phase solidifies and remains in the structural defects.
[0036] In this article, “structural defects” mainly refer to cracks (including microcracks and nanocracks, etc.) and pores.
[0037] In some optional embodiments, the ceramic-fluoride-based composite coating is prepared by thermal spraying, which is exemplarily but not limited to atmospheric plasma spraying, low-pressure plasma spraying, supersonic plasma spraying or supersonic flame spraying.
[0038] In some typical embodiments, the ceramic-fluoride-based composite coating is prepared by atmospheric plasma spraying. The process parameters of the atmospheric plasma spraying include: plasma spray gun current of 450A~650A, argon flow rate of 30L / min~45L / min, hydrogen flow rate of 4L / min~10L / min, spraying distance of 100mm~150mm, and powder feeding rate of 5g / min~25g / min.
[0039] Among them, the plasma spray gun current can be 450A, 480A, 500A, 520A, 550A, 580A, 600A, 620A or 650A, etc., or other values within the range of 450A~650A.
[0040] The argon flow rate can be 30 L / min, 32 L / min, 35 L / min, 38 L / min, 40 L / min, 42 L / min or 45 L / min, etc., or other values within the range of 30 L / min to 45 L / min.
[0041] The hydrogen flow rate may be 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min or 10 L / min, etc., or other values within the range of 4 L / min to 10 L / min.
[0042] The spraying distance may be 100 mm, 110 mm, 120 mm, 130 mm, 140 mm or 150 mm, etc., or may be other values within the range of 100 mm to 150 mm.
[0043] The powder feeding rate can be 5 g / min, 8 g / min, 10 g / min, 12 g / min, 15 g / min, 18 g / min, 20 g / min, 22 g / min or 25 g / min, or other values within the range of 5 g / min to 25 g / min.
[0044] In some optional embodiments, the thickness of the ceramic-fluoride-based composite coating may be 100 μm to 300 μm, such as 100 μm, 150 μm, 200 μm, 250 μm or 300 μm, etc., or other values within the range of 100 μm to 300 μm.
[0045] In the present invention, the ceramic-fluoride based composite coating may include an oxide ceramic-fluoride composite coating, a carbide ceramic-fluoride composite coating or a nitride ceramic-fluoride composite coating.
[0046] The raw materials for preparing the ceramic-fluoride-based composite coating include ceramic particles and fluoride particles.
[0047] Among them, the particle size of the ceramic particles and the fluoride particles can independently be 5μm~75μm, such as 5μm, 10μm, 20μm, 22μm, 25μm, 38μm, 40μm, 52μm, 55μm, 60μm, 65μm, 70μm or 75μm, etc., or other values within the range of 5μm~75μm.
[0048] The mass ratio of the ceramic particles to the fluoride particles may be 1:0.2 to 1:1, such as 1:0.2, 1:0.35, 1:0.39, 1:0.55, 1:0.70 or 1:1, or other values within the range of 1:0.2 to 1:1.
[0049] If the amount of fluoride particles used is too small, the solid lubricating phase of the coating will be less, and it will not be able to produce a good synergistic effect with the solid-liquid reversible lubricating phase, which is not conducive to the lubrication performance of the coating; if the amount of fluoride particles used is too large, the hardness of the coating will be poor, which is not conducive to the wear resistance of the coating.
[0050] Taking the ceramic-fluoride-based composite coating as an oxide ceramic-fluoride composite coating as an example, the ceramic particles in the raw material for preparing the composite coating are oxide ceramic particles. As an example, the oxide ceramic particles may include aluminum oxide particles, and further may include aluminum oxide particles doped with titanium oxide, wherein the doping amount of titanium oxide may be 3wt% by way of example.
[0051] The fluoride particles in the raw material for preparing the ceramic-fluoride-based composite coating may illustratively include soluble polytetrafluoroethylene particles (PFA particles).
[0052] In the present invention, the solid-liquid reversible lubricating phase may exemplarily include at least one of palm wax, microcrystalline wax and stearic acid. In some typical embodiments, the solid-liquid reversible lubricating phase is palm wax.
[0053] It should be emphasized that if lubricating grease is used as the lubricating phase, this type of liquid lubricant mostly has problems such as volatility, easy degradation at high temperature, creep, and the need for sealing during use, and is poor in load-bearing capacity and stability. If a solid lubricating phase is introduced into the structural defects of the coating through in-situ reaction, hydrothermal reaction, etc., the friction reduction performance of the solid lubricant is poor, the energy loss is large, and the in-situ synthesis process is complicated, and the solid lubricant cannot be completely filled in the defects. The hydrothermal reaction process has high equipment requirements, poor safety, and the reaction effect cannot be observed, so the effect is difficult to guarantee. In terms of corrosion protection, traditional thermal spraying ceramic coatings often use paraffin or organic resin as a sealing agent to seal the surface defects to block the corrosive medium and prevent corrosion of the coating and the substrate. However, the sealing effect of the brushing process is poor, it is difficult to completely seal small defects, and the sealing depth is insufficient, and the anti-corrosion effect is poor.
[0054] The present invention specifically adopts a solid-liquid reversible lubricating phase, which can, after heating and melting, fully penetrate into the pores and cracks of the intermediate material (especially into nanoscale defects) through vacuum impregnation, and then solidify in situ and remain at the penetration location after cooling and solidification, thereby effectively solving and avoiding the problems existing in the above-mentioned liquid lubricants or solid lubricants or brush-coated paraffin sealers.
[0055] In the present invention, the amount of the solid-liquid reversible lubricating phase is not limited as long as it can completely submerge the intermediate material. The amount of the solid-liquid reversible lubricating phase contained in the final self-lubricating strong anti-corrosion composite coating is mainly affected by the structural defects of the intermediate material.
[0056] In some optional embodiments, the heating and melting temperature may be 70° C. to 300° C., depending on the lubricating phase material used.
[0057] In some optional embodiments, the intermediate material may be first subjected to surface polishing, ultrasonic treatment, and drying treatment, and then placed in a liquid formed by heating and melting the lubricating phase.
[0058] The surface roughness of the polished intermediate material may be 0.2 μm, for example. Ultrasonication and drying can prevent floating powder during spraying and abrasive debris generated by polishing from blocking the immersion channel.
[0059] In some optional embodiments, the vacuum impregnation may be performed at a pressure of -0.040 MPa to -0.100 MPa for 40 min to 60 min.
[0060] The pressure of vacuum impregnation may be -0.040 MPa, -0.045 MPa, -0.050 MPa, -0.055 MPa, -0.060 MPa, -0.065 MPa, -0.070 MPa, -0.079 MPa, -0.090 MPa or -0.100 MPa, etc., or other values within the range of -0.040 MPa to -0.100 MPa.
[0061] The vacuum impregnation time may be 40 min, 45 min, 50 min, 55 min or 60 min, etc., or may be other values within the range of 40 min to 60 min.
[0062] If the vacuum impregnation pressure is too low or the vacuum impregnation time is too short, it is not conducive to the solid-liquid reversible lubricating phase to penetrate into the pores and microcracks of the ceramic-fluoride composite coating in the liquid state.
[0063] In continuation of the above, the preparation method of the self-lubricating strong anti-corrosion composite coating provided by the present invention is to use the thermal sprayed ceramic-fluoride composite coating as a template, introduce a solid-liquid reversible lubricating phase, heat and melt the solid-liquid reversible lubricating phase, and then use a vacuum impregnation process to make the solid-liquid reversible lubricating phase penetrate into the inherent pores and cracks inside the ceramic coating, and solidify and remain in the above defects after cooling. The preparation method is simple, fast, and efficient, which is conducive to greatly improving the corrosion resistance of the composite coating while further reducing the friction coefficient of the coating, thereby achieving the unified performance of the tribological properties and corrosion resistance of the thermal sprayed ceramic-fluoride composite coating.
[0064] Correspondingly, the present invention also provides a self-lubricating strong anti-corrosion composite coating, which is prepared by the above preparation method.
[0065] When the self-lubricating strong anti-corrosion composite coating is applied to the friction working condition, the fluoride in the composite coating can form a friction film with low shear strength, high hardness, high elastic modulus and strong resistance to plastic deformation on the friction surface, and the solid-liquid reversible lubricating phase retained in the pores and cracks by vacuum impregnation can play a lubricating role together with the fluoride, and the impregnated solid-liquid reversible lubricating phase can continuously overflow to replenish the lubricating film during the subsequent friction process, and the two lubricating phases jointly ensure that the composite coating is effectively lubricated in both the atmosphere and seawater environments for a long time. In addition, the self-lubricating strong anti-corrosion composite coating provided by the present invention has relatively tortuous pores, making it difficult for the corrosive medium to invade the substrate, and the solid-liquid reversible lubricating phase melts and penetrates into the micro / nanoscale defects of the coating in liquid form under the action of vacuum, and can further block the corrosion channel of the corrosive medium after natural cooling to solid, greatly improving the corrosion resistance of the composite coating, and can still maintain the lubrication function under the atmosphere and seawater after ultra-long corrosion.
[0066] Furthermore, the present invention also provides applications of the self-lubricating and highly anti-corrosion composite coating, for example, it can be used to prepare equipment for use in seawater or seawater-atmosphere alternating environments.
[0067] Correspondingly, the present invention also provides a marine engineering equipment, the preparation material of the marine engineering equipment includes the above-mentioned self-lubricating strong anti-corrosion composite coating.
[0068] For example, the above-mentioned marine engineering equipment may include ships, offshore wind farms or drilling platforms, etc.
[0069] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0070] Example 1
[0071] This embodiment provides a self-lubricating strong anti-corrosion composite coating, and the preparation method thereof is as follows:
[0072] S1: An oxide ceramic-fluoride-based composite coating with a thickness of 300 μm is prepared on the surface of a titanium alloy substrate by atmospheric plasma spraying to obtain an intermediate material.
[0073] The raw materials for preparing the oxide ceramic-fluoride-based composite coating are ceramic particles with a particle size of 5μm to 25μm and fluoride particles with a particle size of 5μm to 25μm, the ceramic particles are commercially available alumina powder containing 3wt% titanium oxide (purchased from Höganäs Ltd, Sweden), and the fluoride particles are commercially available PFA powder (purchased from DuPont). The mass ratio of ceramic particles to fluoride particles is 1:0.75.
[0074] The process parameters of atmospheric plasma spraying include: plasma spray gun current of 550A, argon flow rate of 40L / min, hydrogen flow rate of 8L / min, spraying distance of 120mm, and powder feeding rate of 15g / min.
[0075] S2: polishing the intermediate material to a roughness of 0.2 μm, and then ultrasonic cleaning and drying. The intermediate material obtained in this step is recorded as AT3 / PFA composite coating.
[0076] S3: The solid-liquid reversible lubricant palm wax (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., brand C104041) was heated to above 140°C in a vacuum drying oven to achieve melting, and the dried intermediate material was immersed in the melted palm wax and vacuum impregnated at a pressure of -0.08 MPa for 40 minutes.
[0077] S4: After the immersion is completed, take out the sample and cool it to room temperature, and remove the excess palm wax on the surface of the sample.
[0078] The self-lubricating and strong anti-corrosion composite coating obtained from the sample is an aluminum oxide-titanium oxide-palm wax-based composite coating, named AT3 / PFA / CW composite coating, wherein AT3 is aluminum oxide-3wt.% titanium oxide; PFA is soluble polytetrafluoroethylene; and CW is palm wax.
[0079] In this embodiment, the cross-sectional scanning electron microscopy image of the AT3 / PFA composite coating obtained in S2 is as follows: Figure 1 As shown in (a) and (b), Figure 1 (b) is Figure 1 A partial enlarged view of (a).
[0080] In this embodiment, the scanning electron microscope image of the AT3 / PFA / CW composite coating obtained in S4 is as follows: Figure 1 As shown in (c) and (d), Figure 1 (d) is Figure 1 A partial enlarged view of (c).
[0081] Depend on Figure 1 It can be seen that through the vacuum impregnation process, the solid-liquid reversible lubrication phase can effectively penetrate into the inherent pores and cracks inside the ceramic coating.
[0082] In this embodiment, the element distribution results in the AT3 / PFA / CW composite coating obtained in S4 are as follows: Figure 2 shown. Figure 2 (a) to (e) correspond to the distribution results of Al, C, Ti, F and O, respectively.
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is that the solid-liquid reversible lubricant is stearic acid (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., brand number S108289).
[0085] The self-lubricating and highly anti-corrosion composite coating obtained from the sample is an aluminum oxide-titanium oxide-stearic acid-based composite coating, named AT3 / PFA / YZ composite coating.
[0086] Example 3
[0087] The difference between this embodiment and embodiment 1 is that the solid-liquid reversible lubricant is microcrystalline wax (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., brand C304667).
[0088] The self-lubricating and highly anti-corrosion composite coating obtained from the sample is an aluminum oxide-titanium oxide-microcrystalline wax-based composite coating, named AT3 / PFA / WJ composite coating.
[0089] Example 4
[0090] The difference between this embodiment and embodiment 1 is that the ceramic particles are commercially available aluminum oxide powder with a particle size of 5 μm to 25 μm (purchased from Höganäs Ltd, Sweden).
[0091] The self-lubricating and highly anti-corrosion composite coating obtained from the sample is an alumina-palm wax-based composite coating, named Al2O3 / PFA / CW composite coating.
[0092] Example 5
[0093] This embodiment provides a self-lubricating strong anti-corrosion composite coating, and the preparation method thereof is as follows:
[0094] S1: A nitride ceramic-fluoride-based composite coating with a thickness of 300 μm is prepared on the surface of a titanium alloy substrate by atmospheric plasma spraying to obtain an intermediate material.
[0095] The raw materials for preparing the nitride ceramic-fluoride-based composite coating are ceramic particles with a particle size of 5μm to 25μm and fluoride particles with a particle size of 5μm to 25μm, the ceramic particles are commercially available silicon nitride powder (purchased from Desheng), and the fluoride particles are commercially available PFA powder (purchased from DuPont). The mass ratio of ceramic particles to fluoride particles is 1:0.75.
[0096] The process parameters of atmospheric plasma spraying include: plasma spray gun current of 450A, argon flow rate of 30L / min, hydrogen flow rate of 4L / min, spraying distance of 100mm, and powder feeding rate of 5g / min.
[0097] S2: The intermediate material is polished to a roughness of 0.2 μm, and then ultrasonically cleaned and dried.
[0098] S3: The solid-liquid reversible lubricant palm wax (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., brand C104041) was heated to above 140°C in a vacuum drying oven to achieve melting, and the dried intermediate material was immersed in the melted palm wax and vacuum impregnated at a pressure of -0.04 MPa for 60 minutes.
[0099] S4: After the immersion is completed, take out the sample and cool it to room temperature, and remove the excess palm wax on the surface of the sample.
[0100] Example 6
[0101] This embodiment provides a self-lubricating strong anti-corrosion composite coating, and the preparation method thereof is as follows:
[0102] S1: A carbide ceramic-fluoride based composite coating with a thickness of 300 μm is prepared on the surface of a titanium alloy substrate by atmospheric plasma spraying to obtain an intermediate material.
[0103] The raw materials for preparing the carbide ceramic-fluoride based composite coating are ceramic particles with a particle size of 5 μm to 25 μm and fluoride particles with a particle size of 5 μm to 25 μm, the ceramic particles are commercially available silicon carbide powder (purchased from Xiangtian), and the fluoride particles are commercially available PFA powder (purchased from DuPont). The mass ratio of ceramic particles to fluoride particles is 1:0.65.
[0104] The process parameters of atmospheric plasma spraying include: plasma spray gun current of 650A, argon flow rate of 45L / min, hydrogen flow rate of 10L / min, spraying distance of 150mm, and powder feeding rate of 25g / min.
[0105] S2: The intermediate material is polished to a roughness of 0.2 μm, and then ultrasonically cleaned and dried.
[0106] S3: The solid-liquid reversible lubricant palm wax (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., brand C104041) was heated to above 140°C in a vacuum drying oven to achieve melting, and the dried intermediate material was immersed in the melted palm wax and vacuum impregnated at a pressure of -0.085 MPa for 50 minutes.
[0107] S4: After the immersion is completed, take out the sample and cool it to room temperature, and remove the excess palm wax on the surface of the sample.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 1 is that only steps S1 and S2 are performed, and the raw material for preparing the composite coating in S1 is only commercially available aluminum oxide powder containing 3 wt% titanium oxide (purchased from Höganäs Ltd, Sweden), that is, it does not contain PFA.
[0110] The self-lubricating and highly anti-corrosion composite coating obtained from the sample is an aluminum oxide-titanium oxide composite coating, named AT3 coating.
[0111] Comparative Example 2
[0112] The difference between this comparative example and Example 1 is that the raw material for preparing the composite coating in S1 is only commercially available aluminum oxide powder containing 3 wt % of titanium oxide (purchased from Höganäs Ltd, Sweden), that is, it does not contain PFA.
[0113] The remaining steps and conditions are the same as in Example 1.
[0114] The self-lubricating and highly anti-corrosion composite coating obtained from the sample is an aluminum oxide-titanium oxide-palm wax-based composite coating, named AT3 / CW composite coating.
[0115] Comparative Example 3
[0116] The difference between this comparative example and Example 1 is that only steps S1 and S2 are performed.
[0117] The self-lubricating and highly anti-corrosion composite coating obtained from the sample is an aluminum oxide-titanium oxide-PFA composite coating, named AT3 / PFA composite coating.
[0118] Comparative Example 4
[0119] The difference between this comparative example and Example 1 is that the pressure of vacuum impregnation is -0.035 MPa.
[0120] Comparative Example 5
[0121] The difference between this comparative example and Example 1 is that the vacuum impregnation time is 35 minutes.
[0122] Comparative Example 6
[0123] The difference between this comparative example and Example 1 is that the mass ratio of ceramic particles to fluoride particles is 1:0.15.
[0124] Comparative Example 7
[0125] The difference between this comparative example and Example 1 is that the mass ratio of ceramic particles to fluoride particles is 1:1.1.
[0126] Test example
[0127] ①. The tribological properties of the composite coatings prepared in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 7 were characterized. Specifically, the prepared composite coatings were tested using a Retc multifunctional friction and wear tester in accordance with ASTM G133-22 standard. The characterization conditions included: the mode was a ball-disc type, the dual ball was a zirconia ball with a diameter of 5 mm, the test used a sliding speed of 15 cm / s, an amplitude of 2.5 mm, and 10,000 cycles. A long-term (10,000 cycles) friction test was carried out under the same load (8N) and the same sliding speed (15 cm / s). The above-mentioned experimental process was carried out at room temperature (25±2°C) and a relative humidity of 70%±10%. The test conditions included atmospheric environment and seawater environment. The test results are as follows: Figure 3 As shown in Table 1, Figure 3 (a) corresponds to the test results of the embodiment in the atmospheric environment, Figure 3 (b) in the figure corresponds to the test result of the comparative ratio under atmospheric environment. Figure 3 (c) corresponds to the test results of the embodiment in seawater environment, Figure 3 (d) in the figure corresponds to the test result of the comparative example in seawater environment.
[0128] Table 1 Average friction coefficient of the composite coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 7
[0129]
[0130] Depend on Figure 3 It can be seen from Table 1 that the average friction coefficient of the AT3 coating prepared in Comparative Example 1 is about 0.69 in the atmospheric environment and about 0.40 in the seawater environment, and both average friction coefficients are relatively high.
[0131] The average friction coefficient of the AT3 / CW composite coating prepared in Comparative Example 2 is about 0.15 in the atmospheric environment and about 0.32 in the seawater environment. That is, the lubrication performance of the AT3 / CW composite coating prepared in Comparative Example 2 is limited in the above two environments.
[0132] The average friction coefficient of the AT3 / PFA composite coating prepared in Comparative Example 3 is about 0.19 in the atmospheric environment and about 0.24 in the seawater environment. That is, the lubrication performance of the AT3 / PFA composite coating prepared in Comparative Example 3 is limited in the above two environments.
[0133] The average friction coefficient of the AT3 / PFA / CW composite coating prepared in Comparative Example 4 is about 0.18 in the atmospheric environment, and the average friction coefficient in the seawater environment is about 0.21. That is, the lubrication performance of the AT3 / PFA / CW composite coating prepared in Comparative Example 4 is limited in the above two environments.
[0134] The average friction coefficient of the AT3 / PFA / CW composite coating prepared in Comparative Example 5 is about 0.17 in the atmospheric environment, and the average friction coefficient in the seawater environment is about 0.24. That is, the lubrication performance of the AT3 / PFA / CW composite coating prepared in Comparative Example 5 is limited in the above two environments.
[0135] The average friction coefficient of the AT3 / PFA / CW composite coating prepared in Comparative Example 6 is about 0.12 in the atmospheric environment, and the average friction coefficient in the seawater environment is about 0.11. That is, the lubrication performance of the AT3 / PFA / CW composite coating prepared in Comparative Example 6 is limited in the above two environments.
[0136] The average friction coefficient of the AT3 / PFA / CW composite coating prepared in Comparative Example 7 is about 0.12 in the atmospheric environment, and the average friction coefficient in the seawater environment is about 0.08. That is, the AT3 / PFA / CW composite coating prepared in Comparative Example 7 has good lubrication performance in the above two environments, but poor wear resistance.
[0137] The average friction coefficient of the AT3 / PFA / CW composite coating prepared in Example 1 in the atmospheric environment is reduced by 47% compared with that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.10; the average friction coefficient of the AT3 / PFA / CW composite coating prepared in Example 1 in the seawater environment is reduced by 70.8% compared with that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to below 0.07. That is, the AT3 / PFA / CW composite coating prepared in Example 1 exhibits excellent friction reduction and lubrication properties in both marine and atmospheric environments.
[0138] The average friction coefficient of the AT3 / PFA / YZ composite coating prepared in Example 2 in the atmospheric environment is reduced by 21% compared with the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.15; the average friction coefficient of the AT3 / PFA / YZ composite coating prepared in Example 2 in the seawater environment is reduced by 62.5% compared with the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.09. That is, the AT3 / PFA / CW composite coating prepared in Example 2 can also exhibit better friction reduction and lubrication performance in marine and atmospheric environments.
[0139] The average friction coefficient of the AT3 / PFA / WJ composite coating prepared in Example 3 in the atmospheric environment is reduced by 42% compared with that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.11; the average friction coefficient of the AT3 / PFA / WJ composite coating prepared in Example 3 in the seawater environment is reduced by 66.7% compared with that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.08. That is, the AT3 / PFA / WJ composite coating prepared in Example 3 can also exhibit better friction reduction and lubrication performance in marine and atmospheric environments.
[0140] The average friction coefficient of the Al2O3 / PFA / CW composite coating prepared in Example 4 in the atmospheric environment is also lower than that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.15; the average friction coefficient of the Al2O3 / PFA / CW composite coating prepared in Example 4 in the seawater environment is also lower than that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.08. That is, the Al2O3 / PFA / CW composite coating prepared in Example 3 can also exhibit better friction reduction and lubrication performance in marine and atmospheric environments.
[0141] The average friction coefficient of the Si3N4 / PFA / CW composite coating prepared in Example 5 in the atmospheric environment is also lower than that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.12; the average friction coefficient of the Si3N4 / PFA / CW composite coating prepared in Example 5 in the seawater environment is also lower than that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.07. That is, the Si3N4 / PFA / CW composite coating prepared in Example 5 can also exhibit better friction reduction and lubrication performance in marine and atmospheric environments.
[0142] The average friction coefficient of the SiC / PFA / CW composite coating prepared in Example 6 in the atmospheric environment is also lower than that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.12; the average friction coefficient of the SiC / PFA / CW composite coating prepared in Example 6 in the seawater environment is also lower than that of the AT3 / PFA composite coating prepared in Comparative Example 3, specifically reduced to 0.08. That is, the SiC / PFA / CW composite coating prepared in Example 6 can also exhibit better friction reduction and lubrication performance in marine and atmospheric environments.
[0143] ②, the composite coatings prepared in the above Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to EIS characterization, specifically, the composite coatings prepared were subjected to EIS characterization using a CS350M electrochemical workstation in accordance with ISO 16773-1:2016 standard, and the characterization conditions included: a saturated calomel electrode as a reference electrode, graphite as an auxiliary electrode, a coating as a working electrode, and a working area of 1.0 cm 2 The open circuit potential scanning time was 1800s~7200s, the potential scanning rate of the potentiodynamic polarization curve was 1mV / s, and the electrochemical impedance spectroscopy (EIS) test was performed at the open circuit potential with a frequency range of 10 4 ~10 -1 Hz, AC disturbance amplitude is 2mV. Test results are as follows Figure 4 And as shown in Table 2.
[0144] Figure 4 (a) corresponds to the Nyquist plot of the AT3 / CW composite coating prepared in Example 2. Figure 4 (b) corresponds to the Nyquist plots of the AT3 / PFA / YZ composite coating prepared in Example 2 and the AT3 / PFA / WJ composite coating prepared in Example 3. Figure 4 (c) corresponds to the Nyquist plots of the AT3 / PFA / CW composite coating prepared in Example 1 and the Al2O3 / PFA / CW composite coating prepared in Example 4. Figure 4(d) corresponds to the Nyquist plot of the AT3 coating prepared in Example 1 and the AT3 / PFA composite coating prepared in Example 3. Figure 4 (e) is the Bode diagram of the above-mentioned AT3 / CW composite coating, AT3 / PFA / YZ composite coating, AT3 / PFA / WJ composite coating, AT3 / PFA / CW composite coating, Al2O3 / PFA / CW composite coating, AT3 coating and AT3 / PFA composite coating. Figure 4 (f) in the figure is the Bode phase diagram of the above-mentioned AT3 / CW composite coating, AT3 / PFA / YZ composite coating, AT3 / PFA / WJ composite coating, AT3 / PFA / CW composite coating, Al2O3 / PFA / CW composite coating, AT3 coating and AT3 / PFA composite coating.
[0145] Table 2 Modulus table of composite coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 3
[0146]
[0147] Depend on Figure 4 It can be seen from (e) and Table 2 that the modulus values of the AT3 / PFA / CW composite coating, AT3 / PFA / YZ composite coating, AT3 / PFA / WJ composite coating and Al2O3 / PFA / CW composite coating prepared in Examples 1 to 4, respectively, are more than 1000 times higher than that of the AT3 / PFA composite coating prepared in Comparative Example 3, indicating that the corrosion resistance of the composite coating prepared in the embodiments of the present invention is significantly improved.
[0148] ③. The composite coatings of Example 1, Comparative Example 2 and Comparative Example 3 after the salt spray corrosion test (performed in a neutral salt spray atmosphere according to GB / T 10125-2021 standard) were characterized for tribological properties according to the method in ① above. The results are as follows: Figure 5 As shown, Figure 5 (a) in the figure corresponds to the test results in the atmospheric environment. Figure 5 (b) in the figure corresponds to the test results in seawater environment.
[0149] Depend on Figure 5 It can be seen that after 4320 hours of salt spray corrosion test, the friction coefficient of the AT3 / CW composite coating prepared in Comparative Example 2 in the atmospheric environment is 0.19, and the friction coefficient in the seawater environment is 0.23, and its lubrication performance has been significantly reduced.
[0150] After 4320 hours of salt spray corrosion test, the friction coefficient of the AT3 / PFA composite coating prepared in Comparative Example 3 was 0.19 in the atmospheric environment and 0.15 in the seawater environment. However, the friction curve was unstable, making it difficult to ensure that it provided effective lubrication for a long time.
[0151] After 4320 hours of salt spray corrosion test, the friction coefficient of the AT3 / PFA / CW composite coating prepared in Example 1 was 0.11 in the atmospheric environment, and the friction coefficient in the seawater environment was below 0.07, indicating that after extremely long-term corrosion, the AT3 / PFA / CW composite coating prepared in Example 1 can still maintain excellent lubrication function in seawater and atmospheric environments, and the friction coefficient is much lower than that of the AT3 / PFA composite coating of Comparative Example 3 and the AT3 / CW composite coating of Comparative Example 2.
[0152] In summary, the preparation method of the self-lubricating and highly anti-corrosion composite coating provided by the present invention is simple, quick and efficient, and can obtain a composite coating that integrates self-lubrication and strong anti-corrosion functions and is suitable for the alternating environment of seawater and atmosphere. The composite coating has a low friction coefficient and excellent anti-corrosion performance, and can be used to prepare marine engineering equipment.
[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a self-lubricating strong anti-corrosion composite coating, characterized in that: The following steps are involved: A ceramic-fluoride-based composite coating is prepared on the surface of a metal substrate to obtain an intermediate material; the intermediate material is placed in a liquid formed by heating and melting a solid-liquid reversible lubricating phase for vacuum impregnation, so that the solid-liquid reversible lubricating phase penetrates into the structural defects of the ceramic-fluoride-based composite coating; Then naturally cool and solidify, so that the solid-liquid reversible lubrication phase solidifies and remains in the structural defects; The raw materials for preparing the ceramic-fluoride-based composite coating include ceramic particles and fluoride particles, the particle sizes of the ceramic particles and the fluoride particles are independently 5 μm to 75 μm, and the mass ratio of the ceramic particles to the fluoride particles is 1:0.2 to 1:1; the fluoride particles are soluble polytetrafluoroethylene particles; the thickness of the ceramic-fluoride-based composite coating is 100 μm to 300 μm; The ceramic-fluoride-based composite coating is prepared by atmospheric plasma spraying; wherein the process parameters of atmospheric plasma spraying include: plasma spray gun current of 450A-650A, argon flow rate of 30L / min-45L / min, hydrogen flow rate of 4L / min-10L / min, spraying distance of 100mm-150mm, and powder feeding rate of 5g / min-25g / min; The solid-liquid reversible lubricating phase is selected from at least one of palm wax, microcrystalline wax and stearic acid; Vacuum impregnation is carried out at a pressure of -0.040MPa to -0.1MPa for 40min to 60min; The self-lubricating strong anti-corrosion composite coating is used for preparing equipment used in seawater or seawater-atmosphere alternating environment.
2. The preparation method according to claim 1, characterized in that: The ceramic-fluoride based composite coating includes an oxide ceramic-fluoride composite coating, a carbide ceramic-fluoride composite coating or a nitride ceramic-fluoride composite coating.
3. The preparation method according to claim 1 or 2, characterized in that: The heating and melting temperature is 70℃~300℃.
4. The preparation method according to claim 1 or 2, characterized in that: The intermediate material is first subjected to surface polishing, ultrasonic treatment and drying, and then placed in a liquid formed by heating and melting a solid-liquid reversible lubricating phase.
5. A self-lubricating and highly anti-corrosion composite coating, characterized in that: The method is prepared by any one of claims 1 to 4.
6. An application of the self-lubricating strong anti-corrosion composite coating as claimed in claim 5, characterized in that: The self-lubricating strong anti-corrosion composite coating is used for preparing equipment used in seawater or seawater-atmosphere alternating environment.
7. A marine engineering equipment, characterized in that: The preparation material of the marine engineering equipment includes the self-lubricating and highly anti-corrosion composite coating as described in claim 5.
Citation Information
Patent Citations
Thermal spray coating with a dispersion of solid lubricant particles
CN103384728A
Method for constructing ceramic-based self-lubricating, high-wear-resistance and strong-corrosion-resistance coating based on thermal spraying technology and application
CN118685728A